Profitability and Growth Analysis by Using Financial Indicators for Zain Iraq Com - Hadi, Mustafa Hasan; Hasan, Maryam Saleh; Lafloof, Salah Abdullah (Technium Social Sciences Journal, 2025)
The objective of this study is to analyze the profitability and growth trend of Zain Iraq Mobile Telecommunications Company to identify where the indicators are unstable in order to recommend correcting these deviations. The indicators of profitability and growth were based on measuring the financial performance of the company which are the most important indicators on the decisions of the company was reliance on those ratios, which included the study period between 2007 to 2016.The performance of the institution has been tested according to these indicators to ensure that the company is going through a period of decline in profits and sales growth. This indicates the extent to which the indicators used in the analysis of the performance of the company.